Adsorption of Pollutants in Sanitary Landfill Leachate Using Granular Oyster Shell and Perlite - Silahudin, Ahmad Nur Solihin; Zawawi Daud (Recent Trends in Civil Engineering and Built Environment, 2026)
Landfill leachate, containing high concentrations of organic and inorganic compounds, can eutrophize aquatic systems and cause toxic effects on fauna. This study aimed to determine the optimum mix ratio for removing COD, Ammonia Nitrogen, and color using granular oyster shell and perlite as absorbent materials. The optimum dosage was 25:15, with removal percentages of 49.67%, 64.09%, and 60.49%. The shaking speed and pH were also optimized. The adsorbent material effectively removed ±50% to 80% of removal COD, NH3-N, and color.